Anodyne therapy versus exercise therapy in improving the healing rates of venous leg ulcer - Ahmed, Emad T.; Maayah, Mikhled F.; Asi, Yaser Omar Mohammad Abu (International Journal of Research in Medical Sciences, 2017)
Objective: The purpose of this study was to determine the best physical therapy program to increase wound healing rates in patients suffering from venous leg ulcer. Methods: Forty patients who had venous leg ulcer for more than 4 weeks and not respondent well to medical treatment. Patients were classified into 4 equal groups 10 of each, Group (1): received 40 minute of monochromatic infrared energy (MIRE), Group (2): received 40 minutes of exercise program consisted of stretching and resisted exercise (RE), Group (3): received 20 minutes of exercise in addition to 20 minutes of resisted exercise (MIRE/RE), and group (4): control group which received conventional therapy of the ulcer. All groups received treatment 5days per week for 12days. Measurements of ulcer surface area and PUSH scale were conducted before treatment, post 6 days of treatment, and after 12 days of treatment. Results: The one way analysis of variance was used to compare ulcer surface area and PUSH score which revealed that both treatment groups (MIRE and RE) had significant (P< 0.05) decrease in ulcer surface area and PUSH scale after 6 and 12days post application of treatment. On the other hand, the combination of MIRE and RE showed a highly significant decrease in ulcer surface area and PUSH score when compared with control or with individual treatment. Conclusion: The results of this study suggest that combination of MIRE to RE is more effective than individual treatment to enhance the healing rate of venous ulcer of the leg.